ANALISIS PENERAPAN MODUL AJAR SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SD NEGERI 2 BOKAT - insiano, dewi angraini; Marto, Hasia; Nasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was prompted by the crucial role of teaching modules in supporting the Merdeka Curriculum, yet its implementation at SD Negeri 2 Bokat has not been optimal. This study aims to analyze the application of teaching modules as an implementation of the Merdeka Belajar curriculum at the school. This research used a descriptive qualitative approach. Data were collected through interviews with the fourth-grade teacher and the principal, observation of the learning process, and documentation of teaching materials. The results show that the application of teaching modules at SD Negeri 2 Bokat has successfully covered three main components: general information, core components, and appendices. The implementation has been proven to support effective, productive, and meaningful learning. Although some shortcomings were identified, they were overcome through the teacher's innovative approach, adapting the module's content to student characteristics and school conditions. With the dedication of the teacher and support from the principal, the application of the teaching module runs optimally and positively impacts student development.